Analisis Pelayanan Publik Di Kantor Pelayanan Terpadu Kabupaten Rokan Hilir ( Studi Kasus Tentang Pengurusan Surat Izin Tempat Usaha ) Tahun 2013 - MASNOER "; ISHAK " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to analyze the Public Service in the Office of IntegratedServices Rokan Hilir (Case Study On Handling Business Permit). And to knowthe obstacles - obstacles or constraints on the Public Service in the Office ofIntegrated Services Rokan Hilir. Improved Infrastructure as a new district isabsolutely necessary. To support the program, the indispensable role of the privatesector because the private sector is also a supporting actor in the implementationof development regardless of the government in control, it will encourage newbusiness climate. The emergence of a variety of businesses - the business gets theattention of the Government, so that the business - the business community and berecognized by the local government. One of the forms of government recognitionis with the location permit (SITU).This research was conducted in Rokan Hilir, defined in this study as manyas 4 key informants KPT Head, Head of Administration, Economics andAdministration Section Chief and Section Head of Development and Welfare,while people who are taking care of and has been assigned to take care of as manyas 20 people each one with data collection derived from documentations and indepthinterviews to the informant. Once the data is collected and then analyzedusing qualitative descriptive analysis. It can be concluded from the lack ofavailability of good access from OPT Rokan Hilir is not available it means thatsuch a complete lack of waiting rooms and computers for employees to performthe work. To KPT must increase facilities and infrastructures so that people feelcomfortable in the care of the maintenance of location permit (SITU).Keyword : Public Service, SITU.